REPETITION AND HESITATION IN DELIVERING IMPROMPTU SPEECH - Maria Astri Hutabarat and Syamsul Bahri (LINGUISTICA, 2015)
This study deals with the types of repetition and hesitation in deliveringimpromptu speech. The objectives of the study were to describe the kinds ofrepetition and hesitation which used in impromptu speech and why the repetitionand hesitation used in delivering impromptu speech. This research applieddescriptive quantitative method. The source of data was impromptu speech ofEnglish Education class b 2012. Documentary recording as the instrument tocollect the data and there were five students to deliver impromptu speech. Thedata were taken from the utterance of five speechs in impromptu speech intoclauses.There were topics prepared for five topics, each speaker varied oneanother to deliver impromptu speech.The speakers were given 3-5 minutes(maximum) to deliver impromptu speech. Based on the analysis, there were 61utterances of repetition, the result of the analysis showed that two kinds ofrepetition; 59.01% of false start and 40.59 % of parentherical remark. And 205utterances of hesitation, the result of the analysis showed that three kinds ofhesitation; 28.78% of filled pause, 43.90% of silent pause and 27.31% oflengthening. The reason why the repetition and hesitation used in impromptuspeech because the speakers forgot the words when they were talking or speakerare looking for the right words. Not everyone could speak fluently for all topics ofimpromptu speech. In general, people were talking, thinking that the hesitationwas more difficult than repetition.